“An international experience in an English class is…”: An examination of postgraduate students’ perspectives - Daron Benjamin Loo (Thammasat University, 2025)
It is important to understand students’ perspectives about their international experience in an English class because this would help practitioners in their teaching practice and material development. In this study, these perspectives were collected through an open-ended questionnaire that was distributed to 35 groups of international postgraduate students. All these students were enrolled in an academic writing course at a university in Singapore. The questionnaire asked participants for their thoughts and opinions on English lessons that were designed with an international focus. The data was then analyzed through a corpus tool, which identified recurring words. The contextual meanings of these recurring words were then thematized. The main findings saw the themes of “different yet inclusive”; “spurring improvements in writing”; and “learning affordances through native language”. These themes indicated that the participants viewed the international experience as bringing together different perspectives, including an extent of local knowledge and practices. The latter was exemplified through the use of their native language to better understand academic communication in English. Nonetheless, the findings also point towards an ideological tension as postgraduate international students would still need to develop an acceptable level of English language proficiency. This study thus highlights the complexities involved in creating an inclusive and effective English for academic purposes (EAP) course as part of an international experience at the university.